Creating Honeycomb Structures in Porous Polymers by Osmotic Transport. Issue 5 (23rd January 2017) - Quell, Aggeliki; Heitkam, Sascha; Drenckhan, Wiebke; Stubenrauch, Cosima
Abstract: Understanding why honeycombs are shaped the way they are has moved biologists, physicists, chemists, and mathematicians alike.1 2 3 4 5 It was only recently that the honeycombs′ shape "at birth" was included in the ongoing discussions: at birth, the cells are spherical but then transform into the well‐known hexagons. It was proposed that a flow of wax—driven by surface tension effects—is the reason for this transformation.5 Our recent work on synthetic polymer foams with honeycomb‐like structures points towards a very different mechanism. Just like in honeycomb cells, we observe that a spherical "initial state" transforms into a hexagon‐shaped "final state" during polymerization. We have experimental evidence that a concentration gradient arises during polymerization, which transports monomers such that the spherical template becomes a honeycomb structure with walls of homogeneous thickness. The knowledge about this mechanism suggests promising strategies for the development of lightweight materials with optimized mechanical properties. Abstract : An osmotic‐driven transport mechanism causes the formation of honeycomb‐like structures in porous polymers and might apply to bees′ honeycombs as well.